DISKRIMINASI DALAM PENANGANAN PERKARA PIDANA PADA TERSANGKA DIKAITKAN DENGAN ASAS EQUALITY BEFORE THE LAW - Putri Nur Arafah; Emilda Firdaus; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The principle of equality in law or what is often referred to as equalitybefore the law, is interpreted dynamically and is believed to guarantee access tojustice (access to justice) for all people regardless of background. In the contextof the rule of law, the institution that is most highlighted is the judiciary. As one ofthe characteristics of a rule of law state, the judiciary must be independent andimpartial or impartial. An independent judiciary is essentially related to thedesire to obtain the fairest possible decision through the considerations andauthority of an independent judge without the influence or interference of otherparties. Failure to properly implement the principle of equality before the law canlead to injustice in the future. Solving a legal problem.This study aims to determine the forms of discrimination in the Handlingand Treatment of Criminal Offenders associated with the Principle of EqualityBefore the Law and to determine the ideal application of the Principle of EqualityBefore the Law in Handling and Treatment of Criminal Offenders. The researchmethod used is normative legal research method.The results of the study show that differences in status and influence canmake people with the same case not receive the same treatment. One example of acase where 2 (two) perpetrators who both have small children should beconsidered by law enforcement. This is because one of them is a public figure whohas influence and status, so that his “voice” in court is heard more. While theother perpetrators had no influence and status, therefore the courts seemed toturn a blind eye to them. There are a number of factors that influence thejudiciary which impede the fulfillment and implementation of Equality Before theLaw such as economic problems and citizen education as connoisseurs of justice,even education problems are also a problem among law enforcers. Politicalproblems also arise as a suppression of the judicial process, especially incriminal cases.Keywords: Discrimination, Handling Criminal Cases, Equality Before The Law